Information Overload: The Effects of Large Amounts of Information - Mahdi M.N.; Ahmad A.R.; Ismail R.; Subhi M.A.; Abdulrazzaq M.M.; Qassim Q.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
There is an immense amount of information available on the web. In no small part, this wealth of knowledge has challenged scientists continued to search for ways to make the information as easy as possible for end-users. Exploratory quest is transparent and has many characteristics that allow users to find relevant information and to improve their comprehension of the task involved. A comprehensive study is performed on various findings focused on the solutions to the overload issue and has shown that the use of faceted filters minimizes the abundance of information. This paper also discusses information overload and exploratory testing features, such as facial scanning, which can mitigate the effect of clear marine filters. 2020 IEEE.